Mecanica Fluidelor. Note de curs: ISBN 978-606-95069-7-4 - Scurtu, Ionut Cristian (Technium Books, 2022)
Mecanica Fluidelor. Note de curs Note de curs destinate studentilor din domeniul ingineresc cu un continut adaptat nevoilor de invatare ale anului 2022. Technium Books publish all content in open access, promoting the exchange of ideas and knowledge in a globalized world. Technium Books encompasses all the benefits of open access—high availability and visibility, as well as wide and rapid dissemination. Technium Books are distributed under the terms and conditions of the Creative Commons Attribution License — as an author, you retain the copyright for your work. Technium Books believes that the contemporary wave in academia of wider and faster dissemination of knowledge with open access should not be restricted to academic journals but should also capture and elevate academic & research book publishing. See visitor map: https://clustrmaps.com/site/1bg5q